COLLABORATIVE GOVERNANCE DALAM PENERAPAN KEBIJAKAN PEMBERLAKUAN PEMBATASAN KEGIATAN MASYARAKAT (PPKM) DI KOTA PEKANBARU TAHUN 2021 - Ali Yusri; Rico Purnawandi Pane; Syahroni Albi; Adinda Moreta (Journal Publicuho, 2022)
The decline in the PPKM level that occurred in Pekanbaru City from a high status to a normal level is interesting for further discussion. This study aims to explain and analyze government collaboration in the implementation of the Policy for the Enforcement of Community Activity Restrictions (PPKM) implemented in Pekanbaru City in 2021. In this case, the author uses a qualitative approach with sources of information derived from information from informants (community), journals. research journals, and news available on online mass media that have been proven for their credibility. The entire data obtained by the author through interviews, observations, and document tracing were then analyzed using the collaborative governance process theory. The results of the study indicate that in the successful implementation of PPKM policies in Pekanbaru City, there is a series of collaborations carried out by stakeholders involved in the success of the policies implemented, be it the central government, local governments, POLRI, TNI, Satpol PP, medical personnel to the community. Based on the results of the study, it was concluded that the involvement of all stakeholders had a good influence on the continuity of the PPKM policy in Pekanbaru City at this time. It can be said that collaboration plays an important role in the successful implementation of public policy in an area.